Novel devices to monitor heart failure and minimize hospitalizations. (2nd August 2016) - Papavasileiou, Lida Pieretta; Santini, Luca; Forleo, Giovanni B.; Ammirati, Fabrizio; Santini, Massimo
ABSTRACT: Introduction : Approximately 1-2% of the adult population in developed countries is affected by heart failure. The costs of heart failure are enormous both in Europe and in the US and are expected to rise. New technologies and remote monitoring, are valid tools for the management and treatment of these patients. Areas covered : This review aims to cover both implantable and non-implantable devices available for monitoring various hemodynamic parameters and clinical features of patients, as well as algorithms implemented in the new generation ICDs and CRTs capable of simultaneous acquisition and transmission of multiple parameters that indirectly evaluate clinical and/or hemodynamic status. Both internet and PubMed searches were used in order to acquire the most recent developments in the technology of the field. Expert commentary : As new technology offers an enormous data flow, the key for success in the battle against heart failure and related hospitalizations is understanding the correct way of utilizing the data acquired and their importance for the treatment of each individual person.